Implementation of Synchronous Messaging with Visual Basic as a Support for Learning the Parallel and Distributed Systems Course - Nasution, Muhammad Romi; Basorudin, Basorudin (Internet of Things and Artificial Intelligence Journal, 2025)
There are two types of message delivery, namely synchronous and asynchronous messages. Synchronous communication refers to communication that occurs directly and simultaneously, where both parties interact in real-time. Common examples of synchronous communication in online learning include video conferencing, web conferencing, and live chat. Asynchronous communication, which is indirect, allows for more flexible learning through tools such as discussion forums, emails, and blogs. In this article, a chatting application will be designed and built as part of the implementation of the parallel and distributed systems course to support student learning. The application was built using Visual Basic software with important supporting components such as Winsock, TCP/IP protocol, and Local Port, to communicate directly (synchronously) between the client and server. From the test results of conducting chatting between the server and client, it can be concluded that the application runs well as expected without any errors, with an error rate of 0% and a success accuracy rate of 100%. For future researchers, this application can be used as teaching material in the parallel and distributed systems course, and can be developed with other models and the latest software, for example, not only sending messages but also sending files such as images and the like. This research approach can look at multiple sides, for example, from AI-Enhanced Communication, Hybrid Legacy-Modern Integration, Adaptive Protocol Switching, Dynamic Key Exchange, Auto-Discovery Port Management, ML-Optimized UI Components, Context-Aware UX, Predictive Load Balancing, Behavioral Pattern Analysis, AI-Assisted Bug Detection, QoE Assessment Model, dan Open Source Framework.